Effect of severe acute pancreatitis on pharmacokinetics of Da-Cheng-Qi Decoction components - Gong, Han-Lin; Tang, Wen-Fu; Yu, Qin; Xiang, Jin; Xia, Qing; Chen, Guang-Yuan; Huang, Xi; Liang, Mao-Zhi (World journal of gastroenterology : WJG, 2009)
AIM：To investigate the effect of severe acute pan- creatitis（SAP）on pharmacokinetics of Da-Cheng-Qi Decoction（DCQD）components in rats. METHODS：Rats were divided into SAP group and sham-operation group as a control group（n=6）. Rhein,chrysophanol,rheochrysidin,magnolol,hesperidin and naringin in DCQD were quantified in rat serum by high performance liquid chromatography tandem mass spectrometry for studying their pharmacokinetics. RESULTS：Early absorption of each DCQD component was tended to degrade in SAP group after treatment with DCQD by gavage.The Cmax（chrysophanol,P= 0.0059;rheochrysidin,P=0.0288;magnolol,P= 0.0487;hesperidin,P=0.0277;naringin,P=0.0023） and AUC（rhein,P=0.0186;chrysophanol,P=0.0013; magnolol,P=0.001;hesperidin,P=0.0081;naringin, P=0.0272）of DCQD component were obviously lower in SAP group than in control group.The T1/2α of chrysophanol and rheochrysidin（P=0.0467 and 0.0005,respectively）and Tmax of chrysophanol and rheochrysidin（P=0.0101 and 0.0037,respectively） lasted longer in SAP group than in control group. CONCLUSION：SAP can significantly impact the ab-sorption of DCQD components in rats and their phar-macokinetic parameters.